Dampak Disiplin dan Tanggung Jawab Terhadap Kinerja Organisasi Penerbangan: Analisis Kuantitatif dan Implikasi Strategis - Simbolon, Suse Lamtiar; Risqi Wahyu Jati Utama; Axel Yuan Andry Sihite; Siagian, Rory Nicolay; Simaremare, Tonggo Christian (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
This study comprehensively examines the impact of work discipline and employee responsibility on organizational performance in Indonesia’s post-pandemic aviation sector. A quantitative explanatory method was employed by distributing structured questionnaires to 150 employees from three major airlines. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 to test model validity and hypotheses. The results indicate that work discipline has a significant positive effect on organizational performance (β=0.48, p<0.001), followed by responsibility (β=0.32, p<0.01). These findings reinforce contemporary human resource management theory, that a culture of discipline and accountability is a critical determinant in enhancing productivity, particularly in high-risk industries such as aviation. Practical implications include recommendations for competency-based training, transparent reward punishment systems, and the integration of HRM technology to monitor SOP compliance.